Risk factors for postoperative infectious complications after RIRS treatment of kidney and ureteral stones - Stachura, Tomasz; Bąk, Sebastian; Budzeń, Kamil; Wesołowski, Paweł; Gładysz, Konrad; Marzęda, Magdalena; Blicharz, Agnieszka; Sygacz, Oliwer (Journal of Education, Health and Sport, 2022)
Abstract Introduction and aim of the study: Urolithiasis is a disease involving the formation of deposits in the lumen of the urinary tract. The continued development of minimally invasive treatment methods allows for more effective treatment with greater operator comfort and less risk to the patient. It has been concluded that retrograde intrarenal surgery (RIRS) is superior to other therapeutic methods in many respects. The aim of this study is to review the available studies and publications and to identify potential complications following treatment of kidney and ureteral stones by RIRS, with a particular focus on infectious complications and their risk factors. Method and materials: We reviewed the literature available on PubMed and Google Scholar, using the words ’urolithiasis’; ’urolithiasis treatment’; ’retrograde intrarenal surgery’; ’infectious complications of retrograde intrarenal surgery’. Results: Among the risk factors associated with infectious complications after RIRS, long duration of surgery, recent positive urine culture, urinary tract infections or antibiotic use, purulent urine, urinary nitrites, obstructed access through the ureter, struvite stones, co-morbidities play a special role. Conclusions: Among the complications of surgical treatment of nephrolithiasis and ureteral stones by RIRS, infectious complications are of particular concern. In view of the knowledge of their risk factors, preventive measures should include limiting the duration of surgery, possible antibiotic therapy and considering the use of a larger diameter UAS. This is especially true for patients with abnormal urine results, struvite stones, a history of urinary tract infection or predisposing comorbidities. Key words: Urolithiasis; Kidney Calculi; Retrograde Intrarenal Surgery; Urolithiasis infection;